Changing places and identity construction: subjective introspection into researcher's personal destination experiences. Issue 4 (5th October 2015) - Arch G. Woodside, Professor; Batat, Wided
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to draw on a subjective personal introspection (SPI) approach and Breakwell's identity process theory (IPT) principles to show how elements from different cultures are performed by an individual to form a unique patchwork identity, and how this patchwork identity will contribute to deepen tourist gaze and, thus, achieving and maintaining authentic destination experience. Design/methodology/approach – The use of SPI gives the researcher an easy access to data collection of his personal, daily experiences related to changing destinations and consuming different places in Europe (France, UK and Italy), North America (USA and Canada) and North Africa (Algeria, Morocco and Egypt) for unlimited 24-hour access from an insider's ongoing lived experiences. Findings – The results show that Breakwell's IPT four principles are an integral part of patchwork identity construction when living and experiencing several places. Patchwork identity encompasses the individual's ability to cross different social and symbolic boundaries when experiencing different destination. Each cultural context contributes to the bricolage and the assemblage of individual patchwork identity revealing one or more IPT dimensions. Practical implications – This paper serves to emphasize the importance of SPI-based research to patchwork identity construction in understanding the impact of cultural identity on tourist gaze. This approach can help marketers and tourism professionals to understand how consumers select the cultural elements that fit their identity and how the patchwork identity formed will contribute to deepen tourist gaze and destination experience of authenticity. Originality/value – The use of IPT and SPI-based research to explore tourist gaze offers a comprehensive framework based on a personal introspective approach where the starting point is the meaning individual provides to his hyphenated identity as coping mechanism to respond to social, psychological, ideological, cultural, symbolic, functional, structural, etc., aspirations.